Ang siyudad ng mall ang bakod, bukod, at buklod bilang espasyo at biswal mula Tabuan hanggang SM City North Edsa - Nuncio, Elizabeth Morales (Manila De La Salle University Publishing House, 2012)
History and development of the concept of malls in the Philippines.
Keywords: SM City North Edsa -- Design; Shopping malls -- Social aspects -- Philippines; Shopping malls -- Case studies. -- Philippines -- Quezon City; Social ecology -- Philippines -- Quezon City